Vertical photon sorting by stacking silicon and germanium nanopillars for broadband absorbers - Xu Rongyang; Morimoto Takumi; Takahara Junichi (Nanophotonics)
Perfect absorbers based on all-dielectric metasurfaces exhibit great potential in photodetection, photovoltaics, and imaging applications. This study proposes and demonstrates an all-dielectric broadband absorber comprising subwavelength-thick nanopillar Mie resonators in the visible light range. This nanopillar functions as a perfect absorber based on degenerate critical coupling with a characteristic “degenerate critical length.” At this length, the nanopillars are capable of achieving perfect absorption. Beyond this length, the peak of perfect absorption is not affected with further increases in the length of the nanopillars. Hence, this study realizes broadband absorption via the stacking of amorphous silicon and germanium nanopillars with the same width at different peak absorption wavelengths. The absorption spectra are almost independent of the order of the stacked structures; hence, the stacked nanopillars in the specific stacking order can behave as a vertical photon sorter, sorting photons based on the wavelength. This study provides a systematic route to the realization of broadband absorbers with vertical photon sorting capability via the vertical stacking of nanopillars.